Radiological–pathological correlation of negative CT biopsy results enables high negative predictive value for thoracic malignancy. Issue 1 (January 2021) - Barnett, J.; Pulzato, I.; Javed, M.; Lee, Y.J.; Choraria, A.; Kemp, S.V.; Rice, A.; Jordan, S.; Shah, P.L.; Nicholson, A.G.; Padley, S.; Devaraj, A.
Abstract : AIM: To evaluate multidisciplinary team (MDT) practice of radiological–pathological correlation of non-malignant biopsy results to examine the additive effect on the predictive values of computed tomography (CT) biopsy for malignancy and their subsequent management and outcomes. MATERIALS AND METHODS: A service evaluation of the MDT management of non-malignant lung biopsy results (May 2014– May 2017) was undertaken. RESULTS: Sixty patients had a non-malignant diagnosis on initial CT biopsy. Five patients were lost to follow-up leaving 55 in the final cohort. Forty-eight of the 55 patients had biopsy results classified as potentially non-specific, of which 26 were classified as concordant with radiology (e.g., organising pneumonia with compatible CT features), and 22 were classified as discordant (e.g., non-specific inflammation and yet sufficiently suspicious CT features). Patients with concordant negative pathology showed resolution ( n =19) or stability ( n =6) on imaging follow-up. One lesion demonstrated growth and was proven malignant on surgical resection. Discordant lesions were managed with repeat biopsy ( n =8) or surgical resection ( n =13), with 12 final benign diagnoses and nine malignancies. The negative predictive value of CT biopsy alone was 44/55 (80%), following repeat biopsy was 44/50 (88%), and following radiological–pathological assessment was 32/33 (97%). No patients underwent a shift in stage from time of biopsy to resection. CONCLUSION: Combining radiological–pathological interpretation of negative biopsy results offers superior negative predictive value for lung malignancy without delayed diagnosis of lung cancer. Highlights: Non-malignant thoracic biopsy results should be interpreted in the light of imaging findings. When imaging and histological findings are concordant, conservative management is effective. When imaging and histological findings are discordant, further sampling is warranted.